Radio Geometric Mean Graceful Labeling on Degree Splitting of Cycle Related Graphs - C. David Raj, T. Mary Shalini, K. Rubin Mary (Mathematical Statistician and Engineering Applications, 2021)
A Radio geometric mean graceful labeling of a connected graph G is a bijection µ from the vertex set V(G) to 1,2,3,…,|V(G)| such that for any two distinct vertices u and v of G, . A graph which admits radio geometric mean graceful labeling is called radio geometric mean graceful graph. In this paper, we introduced the radio geometric mean graceful labeling on degree splitting of graphs.